Sb-SnO2-Nanosized-Based Resistive Sensors for NO2 Detection. (8th June 2009) - Krishnakumar, T.; Jayaprakash, R.; Pinna, N.; Donato, A.; Donato, N.; Micali, G.; Neri, G.
Abstract : A study over Sb-promoted tin oxide nanopowders for sensing applications is reported.SnO 2 nanopowders pure and promoted with 5 wt% of antimony were prepared by wet chemical methods and widely characterized by TEM, XRD, and XPS techniques. Thick film resistive sensors were fabricated by depositing the synthesized nanopowders by drop-coating on interdigited alumina substrates. The sensing characteristics of the pureSnO 2 and Sb-promoted sensors for the monitoring of trace level ofNO 2 were studied. The response of the sensors to water vapor was also investigated, revealing that Sb acts favorably eliminating the interference of humidity.